2017
DOI: 10.1038/cddis.2017.232
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine protects rat hypoglossal motoneurons from excitotoxic death via downregulation of connexin 36

Abstract: Motoneuron disease including amyotrophic lateral sclerosis may be due, at an early stage, to deficit in the extracellular clearance of the excitatory transmitter glutamate. A model of glutamate-mediated excitotoxic cell death based on pharmacological inhibition of its uptake was used to investigate how activation of neuronal nicotinic receptors by nicotine may protect motoneurons. Hypoglossal motoneurons (HMs) in neonatal rat brainstem slices were exposed to the glutamate uptake blocker DL-threo-β-benzyloxyasp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 75 publications
1
26
0
Order By: Relevance
“…Although former preclinical studies have indicated that nicotine can protect neurons against insults like excitotoxicity or oxygen/glucose deprivation (Gahring, Meyer, & Rogers, ; More & Dong, ), the present investigation was prompted by the recent observation of nicotine protection against excitotoxicity applied to rat brainstem motoneurons (Corsini et al., , ). There was, however, no report of similar effects on the rat spinal cord, an issue that was explored using an in vitro model of spinal cord injury fully validated in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although former preclinical studies have indicated that nicotine can protect neurons against insults like excitotoxicity or oxygen/glucose deprivation (Gahring, Meyer, & Rogers, ; More & Dong, ), the present investigation was prompted by the recent observation of nicotine protection against excitotoxicity applied to rat brainstem motoneurons (Corsini et al., , ). There was, however, no report of similar effects on the rat spinal cord, an issue that was explored using an in vitro model of spinal cord injury fully validated in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with previous protocols for Ca 2+ imaging (Corsini, Tortora, Rauti, & Nistri, ; Fabbro, Skorinkin, Grandolfo, Nistri, & Giniatullin, ; Sharifullina & Nistri, ), organotypic spinal slices grown in vitro for 3 weeks were incubated with the fluorescent calcium dye Fluo 3‐AM (4 μM, Molecular Probes, Invitrogen, Carlsbad, CA, USA) for 1 hr at room temperature in Dulbecco's modified Eagle's medium. The fluorescent dye was washed out with the same medium containing strychnine (1 μM) and bicuculline (20 μM) for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemistry was performed on 450 μm thick slices as described previously (Corsini et al . ). After stabilization, slices were either immediately fixed in 4% paraformaldehyde for 4 h or were incubated (4 h) in either recording Krebs solution (in m m : 130 NaCl, 3 KCl, 1.5 NaH 2 PO 4 , 1.5 CaCl 2 , 1 MgCl 2 , 25 NaHCO 3 and 12 glucose; pH 7.4; 300–320 mOsm) alone as the sham condition or supplemented with selected drugs and fixed afterwards.…”
Section: Methodsmentioning
confidence: 97%
“…), Ca 2+ overload (Sharifullina & Nistri, ; Corsini et al . ), oxidative stress, mitochondrial damage (Tortora et al . ) and an unfolded protein response (Corsini et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation